Water insecurity is associated with intimate partner violence among female adolescents and youth but not males in rural Tanzania: A cross-sectional study - Nelli Kisliuk; Sarah LaPointe; Sera L. Young; Leah Prencipe; Paul Luchemba; Tumpe Mnyawami Lukongo; Tia Palermo (Taylor & Francis Group, 2024)
Food insecurity increases intimate partner violence (IPV), but less is known about water insecurity (WI) and IPV. We examined the association between household WI and IPV among adolescents and youth in the Mbeya and Iringa regions of Tanzania. The cross-sectional sample comprised 977 males and females aged 18-23 years living in rural, impoverished households. We conducted multivariate logistic regression analyses to estimate the association between experiences of WI [measured by the Household Water Insecurity Experiences (HWISE-4) Scale] and physical and/or emotional IPV (measured by an adapted Conflict Tactics Scale). Overall, WI (HWISE ≥4) was associated with 74% higher odds of any IPV (marginal effects (ME) of 7.8 percentage points (pp)), compared to those not WI. Among females (but not males), WI was associated with 3-fold higher odds of any IPV (OR = 3.00; 95% CI: [1.52, 5.94]; ME  = 14 pp). Compared to non-WI females, WI females had 5- and 2-fold higher odds of IPV (ME = 30.8 and 11.3 pp) among the ever married and never married sub-samples, respectively. The association between WI and IPV among females was attenuated (OR = 1.93; 95% CI: [0.93, 3.97]) when adjusting for household food insecurity. Ameliorating water insecurity is a promising avenue for IPV reduction.